GEOMETRICAL OPTIMIZATION OF DENTAL IMPLANTS WITH REGARD TO OSSEOINTEGRATION - Luboš Řehounek; František Denk; Aleš Jíra (Acta Polytechnica CTU Proceedings)
A newly developed reference dental implant specimen type was subjected to numerical simulations of osseointegration. The goal of these tests was to optimize the geometry of the implant so as to reduce local stress concentrations and provide a better flow of stress through the whole implant body. Conditions for osseointegration were considered when evaluating the anchoring system of the implant in regard to its placement in the human cancellous and cortical bone. Numerical simulations showed that stress concentrations occur mostly in the upper cylindrical part of the implant. By increasing the width of this cylindrical part, we were able to reduce the maximum values of von-Mises stress by 20 %.